2017
DOI: 10.4103/1119-3077.198313
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based detailed evaluation of the anatomy of the human coccyx among Turkish adults

Abstract: The findings are contrary to the conventional knowledge in that the vertebrae shaping the coccyx were completely fused and consisting of a single bone in very few cases. Better understanding of the anatomical variation of the coccyx may be useful for clinicians evaluating patients presenting with conditions in the coccygeal region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 0 publications
4
21
3
1
Order By: Relevance
“…However, unlike the current study, the second most common type in the Polish study was type III. Again, in contrast to the current study, Tetiker et al (13) found type I to be the most common in a Turkish population in the western part of the country. This can be attributed to regional differences, as the current study was conducted in the south east of Turkey, where it is customary for people to sit on the ground.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, unlike the current study, the second most common type in the Polish study was type III. Again, in contrast to the current study, Tetiker et al (13) found type I to be the most common in a Turkish population in the western part of the country. This can be attributed to regional differences, as the current study was conducted in the south east of Turkey, where it is customary for people to sit on the ground.…”
Section: Discussioncontrasting
confidence: 99%
“…All the values were greater in males than females. These morphometric values were similar to those of Tetiker et al (13). Tetiker reports that knowledge of these and other morphologic and morphometric changes in the coccyx would be useful to support clinicians' diagnosis and treatment decisions in cases involving the coccygeal region.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Finally, changes in the sacro-coccygeal angle were measured, as loads applied at the coccyx will rotate this mobile joint, reducing the sacro-coccygeal angle. The angle was defined as the angle between the line drawn from the midpoint of the upper edge of the S1 vertebra and the midpoint of the upper edge of the coccyx (Cx1) vertebra, and the line drawn from the midpoint of the upper edge of the coccyx (Cx1) vertebra with the distal aspect of the coccyx Cx3 vertebra according to (19) (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Direct coccyx radiography along with computed tomography (CT), three dimensional CT, and magnetic resonance imaging (MRI) is used to evaluate patients with coccydynia, which is more frequently observed in women than in men. However, direct radiography is frequently used for evaluation due to its fast results, ease of access, low price, and easy dynamic filming [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%